DEVELOPING DIMENSIONS OF INTERNAL AUDIT QUALITY TO EMPLOYEES AN EXPLORATORY STUDY IN GOVERNMENT BANKS. (World Economics and Finance Bulletin, 2022)
This study aims to know the improvement of audit quality by conducting for employees in government institutions, where a questionnaire was distributed to 60 samples, and logistic regression was used to achieve the objectives of the study and test its hypotheses; the study relied on primary and secondary data
Keywords: Quality; Internal Audit